ANALYSIS OF CONSTRUCTION MANAGEMENT CONSTRUCTION PROJECTS DEVELOPMENT OF FLATS OF TEGAL ALUR DKI JAKARTA - Akhmad Jamaludin; Saihul Anwar; Bukhori Bukhori (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2018)
Location of the development project of Tegal Alur DKI Jakarta KSO.WIKA & CAKRA in the Lingkungan III Tegal Alur West Jakarta coordinates Y: 2500.000 X: 2500.000 (West Jakarta PUPR Office)Project management is an attempt to use limited resources efficiently, effectively and on time in completing a predetermined / planned project. There are 3 activities of the basic functions of project management namely planning, implementation and control. Of the three activities are controlled resources on a project that includes manpower, equipment, materials, money and methods.Analysis of Construction Management of Jakarta TegalAlur DKI Jakarta Project Development Project includes Analysis of Work Implementation Method, Volume Calculation and Budget Plan of Jakarta TegalAlur DKI Jakarta Development Project, Schedule Compilation at TegalAlur DKI Jakarta Flower Housing Project, Cash Flow Analysis On Development Project of TegalAlur DKI Jakarta Flats.This research methodology is composed of several main stages, namely Preparation of Survey and Identification of Field, Seeking primary data and secondary data in related institution and department needed to complete data needed in preparation of thesis, Conducting analysis of data obtained through identification problem and make formulation, Taking conclusions and suggestions from the results of research.With Budget Plan Cost and calculation of workload of Jakarta Flat Development Project TegalAlur DKI Jakarta resulted in Working Time Plan takes 231 days using CPM scheduling method with estimated cost of Rp. 36.690.228.549 Keywords :Project Management, Bar Chart, Curva S, CPM (Critical Path Method)